Mode-Selective Absorption and All-Optical Control Between Two Transverse Modes on Silicon-on-Insulator - Yong Zhao; Yuechun Shi; Jia Li; Pan Dai; Shengping Liu; Long Huang; Jun Lu; Tao Fang; Xiangfei Chen (IEEE Photonics Journal, 2019)
Mode-selective absorption is realized by designing the ridge waveguide structure on silicon-on-insulator combined with two metal titanium (Ti) strips located on the two waveguide edges. The TE1 mode can be much easier to permeate the waveguide edges by designing the waveguide structure carefully. Therefore, the overlap between the TE0 and TE1 modes is reduced in the cross section and then the TE1 mode can be absorbed selectively by Ti strips. According to the opto-thermal effect, the refractive index of the waveguide will increase when the temperature rises. As a result, this waveguide structure can achieve all-optical control between two transverse modes with compact structure and low power consumption. As an example, a novel all-optical switch based on the proposed waveguide structure and Bragg grating was designed and numerically studied. We think the proposed structure may give a new way for all-optical control between two transverse modes, especially for the applications in the integrated mode division multiplexing systems.